2017
DOI: 10.1002/ijgo.12347
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of socioeconomic inequalities in preterm deliveries in Tehran, Iran

Abstract: Objective: To investigate associations between economic inequality in preterm delivery. Methods:The present secondary analysis included cross-sectional data collected in interviews with patients following delivery at 103 hospitals in Tehran, Iran, between July 6 and 21, 2015. Principal component analysis was used to measure the socioeconomic status of participants and the concentration index was used to measure inequalities in preterm delivery among patients of different socioeconomic status.Results: Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This observation has been supported by several other studies conducted in both developed and developing nations 23–25 . However, it is important to note that one study presented conflicting results that contradicted our findings 26 …”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This observation has been supported by several other studies conducted in both developed and developing nations 23–25 . However, it is important to note that one study presented conflicting results that contradicted our findings 26 …”
Section: Discussionsupporting
confidence: 73%
“…[23][24][25] However, it is important to note that one study presented conflicting results that contradicted our findings. 26 Upon conducting a decomposition analysis of the CI, it was revealed that certain factors made substantial positive contributions to the measured inequality in the occurrence of stillbirths in Tehran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the principal component analysis (PCA) was used to construct the economic status of the participants by using household assets. PCA has been widely used in previous studies to measure socioeconomic status [3,8,[23][24][25]. Two classes of variables, including the characteristic of housing (e.g., house ownership and floor area) and possession of assets (e.g., private car, motorcycle, personal computer, Internet access, kitchen, telephone, and central heating machine), were used to construct the wealth score.…”
Section: Measuring Healthcare Services Utilization and Definition Of mentioning
confidence: 99%